P-284 PGE2 Is a Robust Mediator of Chloride and Water Secretion by Human Intestinal Epithelial Cells. (February 2017) - Nagata, Sayaka; Fujii, Satoru; Suzuki, Kohei; Kawamoto, Ami; Ishibashi, Fumiaki; Nakata, Toru; Anzai, Sho; Kuno-Ishii, Reiko; Ito, Go; Shimizu, Hiromichi; Tsuchiya, Kiichiro; Nakamura, Tetsuya; et al.
Abstract : Background: Human intestinal epithelial cells (IECs) play an indispensable role in maintaining proper body fluid balance, partly through their ability to secrete chloride ion. However, in various inflammatory bowel diseases (IBDs), over-secretion of the Cl − is induced in IECs, leading to symptoms such as severe watery diarrhea. Studies have shown that endogenous inflammatory mediators such as prostaglandins or bradykinins may mediate Cl − secretion of IECs. However, their precise ability to induce Cl − and water secretion in patient-derived human IECs remains uncertain. In this study, we employed the quantitative assay model of Cl − and water secretion using human intestinal organoids, that was formerly established by Dekkers et al (Nat Med, 2013). By using organoids that were established from normal subjects or from IBD patients, we examined the effect of various mediators through their swelling response. Methods: Colonic or small intestinal biopsies were derived from patients who underwent diagnostic balloon-assisted enteroscopy. Organoids were established by following the methods described in the previous reports of Sato et al (Gastroenterology, 2011). A total of 38 lines of small intestinal (non-IBD origin, n = 3; IBD origin, n = 20) or colonic organoids (non-IBD origin, n = 4; IBD origin, n = 11) were established from 27 patients. For the semi-high throughput quantitative analysis of the swelling response, a newly developed 3D-scanner was employed. By optimizing the system, the cross-section area of the subject organoids was quantified before and after 30 minutes of stimulant addition. The swelling response was defined as the % ratio of the total cross-section area of the organoids that were acquired before and after stimulation. Results: Consistent with the previous study, addition of forskolin clearly induced rapid swelling of the small intestinal organoids for up to 150%, indicating the induction of Cl − and water secretion by the resident IECs. Among the 6 major endogenous mediators that were tested, PGE2 and VIP showed the highest maximum swelling response of over 150%, compared to ACh, histamine, bradykinin or 5-HT. Also, PGE2 showed the lowest EC50 value both in the small intestinal and in the colonic organoids, reaching down to 26 pM in small intestinal organoids and 46 nM in colonic organoids. Such a high and robust response to PGE2 appeared to be conserved among organoids that were derived from non-IBD and IBD patients. The PGE2 -mediated organoid swelling was completely abolished by replacing the environment into a Cl − free condition. In addition, the present PGE2 -mediated response was partially inhibited by adding chemical inhibitors targeted to CFTR, KCNQ channels, or NKCC1. Finally, the PGE2 -mediated organoid swelling was able to maintain its robust response under inflammatory conditions, as the response was completely unaffected by the co-stimulation of inflammatory cytokines including TNF-α, IFN-γ, IL-1β, IL-6, or IL-22. Conclusions: As PGE2 is often upregulated in the inflammatory environment, it may act as the robust and direct mediator of Cl − and water secretion by human IECs, in the inflamed mucosa of IBD patients.